Pricing of biofuels - Schererová, Barbora; Janda, Karel; Vacek, Vladislav; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
This thesis deals with the issue of first-generation biofuels and their relationships with other chosen commodities such as fossil fuels or biofuels feedstock and financial indicators, utilizing the Minimum Spanning Tree method along with the method of Hierarchical Tree. Apart from the analysis of dataset consisting of 38 weekly price series throughout the period of 2003 – 2020, the thesis overviews the current biofuels – related legislation and is also focusing on relevant research concerning the question of sustainability, ecology and economy of biofuels. The main markets that we inspect are the US, Europe and Brazil. The main conclusion that we draw is that analysed biofuels seem to form quite stable relationships with their main feedstocks during price volatile times. One of the most stable relationships was found between Brazilian commodities and between biodiesel and its feedstocks, while the behaviour of US ethanol does not seem to be that clear and stable.
Vedoucí práce: Karel Janda
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses